Erenumab does not alter cerebral hemodynamics and endothelial function in migraine without aura. (January 2021) - Altamura, Claudia; Viticchi, Giovanna; Fallacara, Adriana; Costa, Carmelina Maria; Brunelli, Nicoletta; Fiori, Chiara; Silvestrini, Mauro; Vernieri, Fabrizio
Objective: To assess whether erenumab influences cerebral vasomotor reactivity and flow-mediated dilation in migraine patients. Methods: Consecutive migraineurs prescribed erenumab at our Headache Centre and age and sex-matching controls were invited to participate in this observational longitudinal study. Patients were evaluated for cerebral vasomotor reactivity to hypercapnia (breath-holding index) in middle and posterior cerebral arteries and for brachial corrected flow mediated dilation at baseline (T0), after 2 weeks from the first erenumab injection (T2) and after 2 weeks from the fourth Erenumab injection (T18). Patients displaying a reduction of at least 50% in monthly migraine days after completing the fourth month of therapy were classified as responders. Results: Sixty patients and 25 controls agreed to participate. Middle and posterior cerebral artery mean flow velocities, breath-holding index and flow-mediated dilation did not differ at T0 and from T0 to T2 in patients and controls. In patients, we neither observed a variation of the explored variables from T0 to T18 nor an interaction between evaluation times (T0–T2 or T0–T18) and chronic condition at T0, responder state or erenumab fourth dose. Conclusions: Our findings demonstrate that erenumab preserves cerebral vasomotor reactivity and flow-mediated dilation in migraineurs without aura.